Ground Penetrating Radar (GPR) data on snow over lakes and drained lake basins in Inigok, North Slope of Alaska, April 2019 - Rodrigo Correa Rangel; Andrew Parsekian; Noriaki Ohara; Benjamin Jones (Arctic Data Center, 2023)
This dataset contains ground penetrating radar (GPR) data acquired between April 27 and 28, 2019, on two drained lake basins (DLBs) [Three Creatures Basin and Deep Basin] and four lakes [Independent Fox Lake, INI01 Lake, INI04 Lake, and Lonely Wolf Lake] at Inigok region in the North Slope of Alaska. The measurements were made using Malå ProEx 800 megahertz (MHz) (GuidelineGeo, Sundbyberg, Sweden) antennas using common offset configuration. Raw GPR data of eight transects are provided in the .RAD3 format, along with the corresponding acquisition parameters (.RAD) and Global Positioning System (GPS) coordinates (.COR) files. A spreadsheet with basic information and a Keyhole Markup Language (KML) file indicating the location of each transect are also provided. This dataset can be used to estimate snow properties.